KELAYAKAN POSTER KEANEKARAGAMAN HAYATI TINGKAT JENIS KELAS X - Tendry Tendry; Entin Daningsih; Titin Titin (Universitas Tanjungpura, 2020)
AbstractThis study aimed to determine the feasibility of poster on various levels of speciesbiodiversity at class X. The form of research was descriptive with purposive samplingtechnique. Poster was evaluated by 5 validator’s using likert scale. There were 4 aspec’san 11 criteria and analist using lawshe method. An average of poster CVR value was0.99 and CVI value was 0,99. Thus, the poster was declared valid or appropriate forusing a medium of learning on the material of species at class X.Keywords: Species Biodiversity, Poster, feasibility